Environmental sensitivity index (ESI) mapping of oil spill in the amazon coastal zone: the PIATAM Mar project - SOUZA FILHO, Pedro Walfir Martins e (2014)
The importance of environmental monitoring is clear from the many oil spills that have occurred over the past three decades. This has encouraged both companies and the public sector involved in the prevention and response to these accidents to develop efficient procedures to minimize the damage caused by accidents involving oil spill. This study reviews the history of oil spill accidents in Brazil and examines how these events have contributed to the development of technological research through partnerships involving oil companies, government, universities and research institutes, with the emphasis on the Amazon coastal zone. As a result, environmental sensitivity indexes (ESIs) for oil spill have been developed specifically for the Amazon coast, where fluvial and marine processes take place in the estuary of the world's largest river system. Perspectives on research and emergency response procedures are presented, with the primary objective of conserving the social-environmental diversity of the planet's most important tropical region.